Low-frequency oscillation damping in the electric network through the optimal design of UPFC coordinated PSS employing MGGP. (May 2019) - Shafiullah, Md; Rana, Md Juel; Shahriar, Mohammad Shoaib; Zahir, Md Hasan
Highlights: MGGP-A novel intelligence approach optimizes the PSS coordinated UPFC parameters. Standard statistical performance measures validate the proposed technique. Results are compared with fixed gain conventional PSS and the referenced work. Abstract: The coordination of flexible AC transmission systems (FACTS) with power system stabilizers (PSS) can significantly enhance the overall network stability by damping out the low-frequency oscillations (LFO). This paper proposes a multi-gene genetic programming (MGGP) approach to optimize PSS parameters coordinated with unified power flow controller (UPFC) to enhance power system stability by damping out LFO. The obtained results (minimum damping ratio, eigenvalues and time domain simulations) of the proposed MGGP approach are compared with the results of the conventional fixed gain model, the single-gene genetic programming (SGGP) approach and the referenced work to inquire the efficacy of the proposed approach for various operating conditions of the considered electric network. Besides, the acceptable values of standard statistical performance measures in estimating UPFC-PSS parameters provide confidence on the evolved MGGP models. Furthermore, the proposed approach requires a minimal time (∼less than a cycle) to estimate the key parameters that signal the real-time application of the proposed technique.